2017
DOI: 10.17161/jas.v3i3.6510
|View full text |Cite
|
Sign up to set email alerts
|

Parental involvement in the lives of intercollegiate athletes

Abstract: The topic of parental involvement in the lives of their children, and the concept of over-involved parents has been growing as an area of research. The current study aims to fill this gap by examining parental involvement in the context of intercollegiate athletics. Specifically, a qualitative case-study method was utilized to examine parents' involvement in the academic and athletic lives of their studentathletes, including a focus on the concept of over-involvement in relationship to this population. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The cell phone is preferred because it enables direct and rapid contact despite geographic distance and because it provides an avenue to share experiences and garner support without infringing upon emerging adults' independence (e.g., Chen & Katz, 2009). Research with SAs has yielded similar findings (e.g., Parietti et al, 2017). About 40% of Dorsch and colleagues' (2016a) sample of Division I SAs reported texting with parents daily and about one-third chatted on the phone a few times a week.…”
Section: Research On Parental Involvement In Intercollegiate Athleticsmentioning
confidence: 98%
See 4 more Smart Citations
“…The cell phone is preferred because it enables direct and rapid contact despite geographic distance and because it provides an avenue to share experiences and garner support without infringing upon emerging adults' independence (e.g., Chen & Katz, 2009). Research with SAs has yielded similar findings (e.g., Parietti et al, 2017). About 40% of Dorsch and colleagues' (2016a) sample of Division I SAs reported texting with parents daily and about one-third chatted on the phone a few times a week.…”
Section: Research On Parental Involvement In Intercollegiate Athleticsmentioning
confidence: 98%
“…For instance, a broad, descriptive report by the NCAA found 81% of SAs across divisions said their family was "appropriately involved" in their academics and about 65% of SAs "often" or "sometimes" asked family to assist with academic decisions (NCAA, 2017b). Interviews with SAs have also revealed that parents help ease the stress associated with poor academic performance (Cosh & Tully, 2015) and serve as consultants for academic and career plans (Parietti et al, 2017). Notably, Dorsch et al (2016a) found academic engagement positively predicted SAs' academic self-efficacy and athletic satisfaction and negatively predicted emotional and functional independence, reiterating the import of appropriate academic engagement.…”
Section: Research On Parental Involvement In Intercollegiate Athleticsmentioning
confidence: 99%
See 3 more Smart Citations